A phylogenetic analysis of Pseudopaludicola (Anura) providing evidence of progressive chromosome reduction - Veiga-Menoncello, Ana C. P.; Lourenco, Luciana B.; Struessmann, Christine; Rossa-Feres, Denise C. [UNESP]; Andrade, Gilda V.; Giaretta, Ariovaldo A.; Recco-Pimentel, Shirlei M. (Wiley-Blackwell, 2014)
Here, we present a molecular phylogenetic analysis of the Neotropical genus Pseudopaludicola focusing on species relationships including 11 of the 17 known species of Pseudopaludicola; several samples of Pseudopaludicola are not assigned to any species; and 34 terminal species as an outgroup. The study was based on the analysis of approximately 2.3kb of the sequence of the mitochondrial 12S rRNA, tRNA(val) and 16S rRNA genes through maximum parsimony and Bayesian phylogenetic reconstruction approaches. Our results showed that Pseudopaludicola is a well-supported monophyletic group organized into four major clades and confirmed that the assemblage of species that lack T-shaped terminal phalanges is paraphyletic with respect to the P.pusilla Group. Chromosomal data mapped on the cladogram showed a direct correlation among the four clades and observed chromosome numbers (2n=22, 20, 18 and 16) with a progressive reduction in the chromosome number. Overall, our findings suggest that some taxonomic changes are necessary and reinforce the need for a revision of the genus Pseudopaludicola.